2022
DOI: 10.3390/foods11193031
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Ten Pear (Pyrus communis L.) Cultivars in Relation to the Content of Sugars, Organic Acids, and Polyphenol Compounds

Abstract: Traditional pear cultivars are increasingly in demand by consumers because of their excellent taste, the possibility of use in sustainable food production systems, convenience as raw materials for obtaining products of high nutritional quality, and perceived health benefits. In this study, individual sugars, organic acids, and polyphenols in the fruits of nine traditional and one commercial pear cultivar during two growing seasons were determined by HPLC. A significant influence of cultivars, growing years, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…Öztürk et al [10] found a content of chlorogenic acid from 21 to 1348.4 mg kg −1 in the peel; the highest values reported in this study were comparable to our results. Akagić et al [9] reported a content of chlorogenic acid from 2.27 to 359.96 mg kg −1 in the peel during two years of observations which is lower than our results. Liaudanskas et al [23] detected and quantified the quercetin 3-O-(6 -O-malonyl)-β-glucoside in the pear samples of different popular cultivars namely Conference, Concordia, Grabova, and Patten.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Öztürk et al [10] found a content of chlorogenic acid from 21 to 1348.4 mg kg −1 in the peel; the highest values reported in this study were comparable to our results. Akagić et al [9] reported a content of chlorogenic acid from 2.27 to 359.96 mg kg −1 in the peel during two years of observations which is lower than our results. Liaudanskas et al [23] detected and quantified the quercetin 3-O-(6 -O-malonyl)-β-glucoside in the pear samples of different popular cultivars namely Conference, Concordia, Grabova, and Patten.…”
Section: Discussioncontrasting
confidence: 94%
“…The wide range was dependent solely on varietal characteristics as environmental and agronomic conditions were the same for all cultivars. A great variation in the content of chlorogenic acid was also observed by Akagić et al [9], who studied Bosnian cultivars from a collection orchard. During two growing years, the chlorogenic acid in the flesh ranged from 0.46 to 14.94 mg kg −1 (first year) and from 0.10 to 9.69 mg kg −1 (second year), and the values were lower than our data.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…They can be used in puddings, pies, tarts, and cakes, as well as caramelized and brandied [ 19 ]. The organoleptic qualities, taste, aroma, composition, and antioxidant properties of pears influence health-conscious customers’ fruit choices [ 20 , 21 ]. Pears are regarded as a hypoallergenic fruit and are high in fiber yet unlikely to have any negative side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they contribute to biodiversity preservation and cherishing of cultural-historical heritage. Various studies have shown that traditional B&H cultivars contain higher polyphenols content in comparison to commercial fruits [19,20].…”
Section: Introductionmentioning
confidence: 99%